(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
A microbial fuel cell (MFC) is a type of device which is an electrochemical, after technology that is being to recover electricity from wastewater. This study’s objective was to measure the potential difference from sludge collected from El-Sheikh Zayed water purification plant (Egypt in April 2021), isolate and identify bacteria present in sludge: Also, determine the effect of adding some metabolites on such physical and chemical properties. Potential difference measurement showed (192 mV) by using MFC. Pantoea spp., Aeromonas salmonicida, Comamonas testosteroni and Staphylococcus lentus were isolated and identified by biochemical reaction tests. A. salmonicida gave the highest potential difference (13mV). After adding some metabolites separately (albumen, dextrose, gelatin and casein), casein recorded 196Mv, a mixture was done between A. salmonicida and four metabolites measuring 50 mV. Physical and chemical analysis showed that biochemical oxygen demand (BOD) (55.0 P.P.M.), chemical oxygen demand (COD) (112.0 P.P.M.), and many minerals and heavy metals were also detected. Green synthesis of electricity from electrogenic bacteria using wastewater like sludge is a promising way to generate electricity by a cheap method.